Microstructure and mechanical properties of thixoformed A319 aluminium alloy - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Syarif, Junaidi; Alhawari, Khalid Salim; Mohammed, Mohamad Naser (Elsevier, 2014)
Thixoforming is a viable technology for forming alloys in a semisolid state into near net-shaped products. In the present study, the effect of a thixoforming process on the microstructure and mechanical properties of A319 aluminium alloy was investigated. The ingots obtained from the cooling slope were thixoformed in a press after they remained at 571 °C for 5 min, yielding a microstructure predominantly composed of α-Al globules and inter-globular Si particles. Some of the thixoformed samples were treated with an ageing process (T6) and then, hardness and tensile samples were prepared from the as-cast, as-thixoformed and thixoformed T6. All the thixoformed samples were characterised using optical microscopy, scanning electron microscopy (SEM), energy dispersive X-ray (EDX) and X-ray diffraction (XRD) as well as hardness measurements and tensile tests. The results indicate that the mechanical properties of the thixoformed A319 alloy increased after the T6 heat treatment (hardness of 124.2 ± 3.2 HV, tensile strength of 298 ± 3.0 MPa, yield strength of 201 ± 2.6 MPa and elongation to fracture of 4.5 ± 0.3%). The fracture samples from the tensile test were analysed, revealing that the iron-rich intermetallic observed in the samples reduced the tensile strength and ductility of the thixoformed A319 alloys.